Globalization And Transfer Of Technology: The Implications For Nigeria's Economic Development - JOHNSON, Marvellous Otega (LPPM Universitas Malikussaleh, 2024)
Although, globalization is relatively not a new conceptï¼Œit is a contemporary one which is used to explain the integration and interaction of governments, inter and non-governmental organisations and individuals on a global scale. The concept of globalization captures the entire world as a global village and a borderless world made possible with the aid of technology. The major and the perhaps the most attractive aspect of the globalization process is the economic aspect, though there are the social and cultural aspects. With the aid of the globalization process, there have been massive exchange of goods and services and mobility of labor across borders and among various countries of the world. Interestingly, there have also been advocacy to use the globalization process to transfer technologies from the advanced developed countries to the third-world developing countries like Nigeria. The paper therefore, examines the tenets of the globalization process, the phenomenon of technology transfer, whether the globalization process has resulted in technology transfer and the extent to which technology transfer has affected Nigerias economic development. This study makes use of secondary data derived from published and unpublished materials and the internet. Methodologically, the historical method was adopted to extract relevant information from past and current events as it relates to the problem of the study while the descriptive method of Data analysis was also used in this study. The findings of the inquiry revealed amongst others that globalization promotes quick economic expansion in Nigeria and it is of benefits to both the public and private sectors of the economy while technology transfer has helped in easing transfer of useful information among individuals, government, institutions and business organizations. The study recommended among others that the Nigerian government should enact legislations and ratify international agreements that can advance globalization and technology transfer. This is so because the benefits of globalization and transfer of technology significantly outweigh its drawbacks.